2018
DOI: 10.3390/su10124488
|View full text |Cite
|
Sign up to set email alerts
|

A Needs-Driven, Multi-Objective Approach to Allocate Urban Ecosystem Services from 10,000 Trees

Abstract: Urban areas face challenges including vehicular emissions, stormwater runoff, and sedentary lifestyles. Communities recognize the value of trees in mitigating these challenges by absorbing pollution and enhancing walkability. However, siting trees to optimize multiple benefits requires a systems approach that may cross sectors of management and expertise. We present a spatially-explicit method to optimize tree planting in Durham, NC, a rapidly growing urban area with an aging tree stock. Using GIS data and a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…In Portland, Oregon, city planners have used MULC to design street tree planting and green infrastructure for urban heat island mitigation [24]. In Durham, North Carolina, EnviroAtlas has been used to identify census block groups with low tree cover and vulnerable populations to explore how tree planting might benefit child development, overall public health, and environmental quality [25,26]. In Tampa Bay, Florida, a Health Impact Assessment (HIA) has demonstrated how MULC and EnviroAtlas metrics, tools, and data can assist decision makers in a health and wellness application [27].…”
Section: Discussionmentioning
confidence: 99%
“…In Portland, Oregon, city planners have used MULC to design street tree planting and green infrastructure for urban heat island mitigation [24]. In Durham, North Carolina, EnviroAtlas has been used to identify census block groups with low tree cover and vulnerable populations to explore how tree planting might benefit child development, overall public health, and environmental quality [25,26]. In Tampa Bay, Florida, a Health Impact Assessment (HIA) has demonstrated how MULC and EnviroAtlas metrics, tools, and data can assist decision makers in a health and wellness application [27].…”
Section: Discussionmentioning
confidence: 99%
“…Correlations are weak, insignificant or negative in more agricultural communities in semi-arid and grassland ecoregions such as Fresno, CA, Des Moines, IA, and Brownsville, TX as well as in cities with high amounts of impervious surface like New York City, NY and Paterson, NJ. These findings need further investigation considering urban vegetation inequity, where neighborhoods with higher levels of income and education often have more woody and mixed vegetation and parks [55]. Though CEHI favors communities and neighborhoods with greater tree cover and greenspace, both ecoregion and urban vegetation inequity need to be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…They manuscript submitted to Water Resources Research suggest a method for including multi-aspects of vulnerability to prioritize green infrastructure projects to provide multi-benefits to underserved communities. Almeter et al (2018) developed a semi-quantitative prioritization scheme to identify a tree planting strategy based on maximizing multi-benefits. They found that multi-objective benefits favored planting in historically disadvantaged U.S. Census block groups in Durham, North Carolina, compared to single objectives.…”
Section: Structural Equitymentioning
confidence: 99%